Significance of Dietary Iron for Human Biological System and Brain Development - Imam, Aminu Umar; Sarkingobir, Yusuf (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2024)
The need for iron in the human biological system is enormous and lack of iron is dangerous especially for children, youngsters, and women due to the role of iron in growth and development among other things. It is important to state that iron is very critical in the functioning of nervous system as well. The aim of this paper is to conduct a review pertaining the significance of iron in humans, and specifically on brain development (cognition, learning and relations). The paper utilized review and conceptual methods to elucidate, advantages of iron chemistry (eg in hemoglobin, myoglobin, cytochromes, iron-sulfur proteinous entities, etc), the effects of iron deficiency or deficits in schooling children and the rest, sources of dietary iron, iron inhibitors or blockers, iron deficiency anemia, iron in the fetal developments and some methods for intervening in iron deficiency.